Analisis Pelanggaran Kontrak Era Digital sebagai Studi Kasus pada Perusahaan PT. ILMCI Indonesia Internasional - Rupais, Andi; Sudarto, Sudarto (FOCUS, 2025)
This research aims to analyse the increasingly complex breach of contract in the digital era, with a focus on the phenomenon of breach of contract that occurs in online transactions. This research was conducted at the company PT ILMCI Indonesia International, with the aim of providing theoretical and practical contributions in developing effective strategies to overcome breach of contract and support the improvement of company performance in the midst of digital challenges. This research uses two methods, namely normative and empirical legal research, to provide a comprehensive analysis of the relationship between legal theory and the practice of breach of contract that occurs in the field. Hopefully, the results of this research can serve as a guide for companies in designing stronger and more legally binding digital contracts.